Inpatient Outcomes for Myocarditis-Related Heart Failure - Alabbas, Mohammad; Gibson, Cheryl; Morad, Abdulrahman; Mohammad Alahmad, Mohammad Alhoda (Avicenna Journal of Medicine, 2023)
Background Heart failure (HF) is one of the leading causes of hospitalizations among adults, accounting for high rates of morbidity and mortality in the United States. Myocarditis is a less common etiology of HF, and its outcomes are less well understood.Methods We used the Nationwide Readmissions Database from 2016 to 2019, extracting adult patients with a primary diagnosis of HF who were admitted between January and November of each year studied. We excluded patients with missing data on event time or length of stay. Inpatient outcomes were compared between cases of HF without myocarditis and myocarditis-associated HF (MAHF). Survey procedures were applied. Propensity scores as covariates were used in survey-weighted models to estimate the population average treatment effect on the treated using SAS 9.4.Results We included 4,454,272 HF-related weighted admissions for which 4,605 patients (0.1%) had a concurrent diagnosis of myocarditis. Overall, patients with MAHF, compared with HF without myocarditis, were younger (mean age: 53 years vs. 72 years, p < 0.001) with fewer women (45 vs. 48%), respectively. Patients with MAHF had more inpatient complications including cardiac arrest, cardiogenic shock, and use of mechanical circulatory support (p < 0.001) despite having fewer comorbidities such as diabetes, hypertension, and renal disease. Patients with MAHF had longer mean lengths of stay (9.2 vs. 5.5 days, p < 0.001). In-hospital mortality during index admission was significantly higher in MAHF at 3.9% compared with 2.8% for HF without myocarditis (p < 0.001). Myocarditis was a key predictor of inpatient mortality adjusting for risk factors.Conclusion Myocarditis-related HF is associated with increased inpatient mortality, resource utilization, and prolonged hospitalization.
Keywords: heart failure; inpatient mortality; myocarditis